Problems of forest management in municipal forests of the city of Poznań = Problemy gospodarki w lasach miejskich na przykładzie obszarów leśnych miasta Poznania - Jaszczak, Roman; Wajchman-Świtalska, Sandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents some selected management problems in municipal forests occurring as a result of the increasing pressure on recreation and urbanization. The object of investigation was municipal forests of the city of Poznań.
Keywords: lasy miejskie; Poznań; rekreacja; presja miejska; gospodarka leśna; municipal forests; recreational pressure; urban pressure; forest management